Determining virus-host interactions and glycerol metabolism profiles in geographically diverse solar salterns with metagenomics - Abraham G. Moller; Chun Liang (PeerJ, 2017)
Solar salterns are excellent model ecosystems for studying virus-microbial interactions because of their low microbial diversity, environmental stability, and high viral density. By using the power of CRISPR spacers to link viruses to their prokaryotic hosts, we explored virus-host interactions in geographically diverse salterns. Using taxonomic profiling, we identified hosts such as archaeal Haloquadratum, Halorubrum, and Haloarcula and bacterial Salinibacter, and we found that community composition related to not only salinity but also local environmental dynamics. Characterizing glycerol metabolism genes in these metagenomes suggested Halorubrum and Haloquadratum possess most dihydroxyacetone kinase genes while Salinibacter possesses most glycerol-3-phosphate dehydrogenase genes. Using two different methods, we detected fewer CRISPR spacers in Haloquadratum-dominated compared with Halobacteriaceae-dominated saltern metagenomes. After CRISPR detection, spacers were aligned against haloviral genomes to map virus to host. While most alignments for each saltern metagenome linked viruses to Haloquadratum walsbyi, there were also alignments indicating interactions with the low abundance taxa Haloarcula and Haloferax. Further examination of the dinucleotide and trinucleotide usage differences between paired viruses and their hosts confirmed viruses and hosts had similar nucleotide usage signatures. Detection of cas genes in the salterns supported the possibility of CRISPR activity. Taken together, our studies suggest similar virus-host interactions exist in different solar salterns and that the glycerol metabolism gene dihydroxyacetone kinase is associated with Haloquadratum and Halorubrum.